2016
DOI: 10.1007/s40616-016-0069-z
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Three Procedures to Teach Echoic Responding

Abstract: The research literature has revealed mixed outcomes on various procedures for increasing vocalizations and echoic responding in persons with disabilities (Miguel, Carr,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
5
0
7
Order By: Relevance
“…Alternatively, the lack of effects in the prompt condition might indicate that the observed target responses may not have been mands. Given that the prompt delivered by the therapist included a model of the target response (e.g., “Remember, you can ask for the iPod® if you want it”), the responses may have functioned as echoics (Cividini‐Motta, Scharrer, & Ahearn, ). This may have accounted for the transient effects during the prompt and PTSP conditions for Alex, Dave, Erik, and Bev.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the lack of effects in the prompt condition might indicate that the observed target responses may not have been mands. Given that the prompt delivered by the therapist included a model of the target response (e.g., “Remember, you can ask for the iPod® if you want it”), the responses may have functioned as echoics (Cividini‐Motta, Scharrer, & Ahearn, ). This may have accounted for the transient effects during the prompt and PTSP conditions for Alex, Dave, Erik, and Bev.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review in the introduction identified some previous studies interested in the teaching conditions of echoic behavior that were not part of this review either because it was adopted as pre-current (Kodak & Clements, 2009), or because participants had other diagnoses besides by ASD (Cividini-Motta, Scharrer, & Ahearn, 2017). Although echoic is an important repertoire to be established, as it may be a condition for the acquisition of other more complex behaviors (Rosales-Ruiz & Baer, 1997), the literature reveals its use mainly as a prompt and in studies with little experimental rigor, which does not support evidence-based practices.…”
Section: Discussionmentioning
confidence: 99%
“…Research further GUERRA, B.T. et al hypothesizes that echoic behavior can facilitate the acquisition of listener behavior (Cividini-Motta, Scharrer, & Ahearn, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Os artigos selecionados para compor a presente revisão sistemática são estudos longitudinais. Os estudos apresentaram 25 participantes, sendo que três envolviam sujeitos do sexo feminino [10][11][12] e os demais contaram exclusivamente com participantes do sexo masculino [13][14][15][16] . Em relação à idade, esta variou de 3,50 10 a 32,50 anos 16 .…”
Section: Características Dos Estudos Selecionadosunclassified